2023
DOI: 10.1021/acs.jpcb.2c07930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Block Sequence on the Solution Self-Assembly of Symmetric ABCBA Pentablock Polymers in a Selective Solvent

Abstract: Solution self-assembly of multiblock polymers offers a platform to create complex functional self-assembled nanostructures. However, a complete understanding of the effect of the different single-molecule-level parameters and solution conditions on the self-assembled morphology is still lacking. In this work, we have used dissipative particle dynamics to investigate the solution self-assembly of symmetric ABCBA linear pentablock polymers in a selective solvent and examined the effect of the block sequence, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…Previous theoretical simulations of the self-assembly process of linear multiblock amphiphilic copolymers have shown that micelle morphologies are highly dependent on factors such as hydrophilic–hydrophobic content in the copolymer, the sequence distribution of hydrophilic and hydrophobic blocks along the copolymer backbone, and copolymer concentration in the solvent . In general, the simulated supramolecular morphologies sought to minimize the amount of exposed solvophobic segments . Interestingly, compared to the spherical micelles structures of previously reported branched PEG–PPG thermogels, these branched PCP and PCPN polymers adopted a different core–shell micelle structures.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous theoretical simulations of the self-assembly process of linear multiblock amphiphilic copolymers have shown that micelle morphologies are highly dependent on factors such as hydrophilic–hydrophobic content in the copolymer, the sequence distribution of hydrophilic and hydrophobic blocks along the copolymer backbone, and copolymer concentration in the solvent . In general, the simulated supramolecular morphologies sought to minimize the amount of exposed solvophobic segments . Interestingly, compared to the spherical micelles structures of previously reported branched PEG–PPG thermogels, these branched PCP and PCPN polymers adopted a different core–shell micelle structures.…”
Section: Resultsmentioning
confidence: 94%
“…The temperature-driven shift toward higher q values is indicative of the micelles packing more compactly together as they dehydrate upon warming during the gelation process. Previous theoretical simulations of the self-assembly process of linear multiblock amphiphilic copolymers have shown that micelle morphologies are highly dependent on factors such as hydrophilic–hydrophobic content in the copolymer, the sequence distribution of hydrophilic and hydrophobic blocks along the copolymer backbone, and copolymer concentration in the solvent . In general, the simulated supramolecular morphologies sought to minimize the amount of exposed solvophobic segments .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 While not explicitly dealing with the precise manipulation of monomer sequence, dissipative particle dynamics simulations have shown differences in self-assembled structures based on block sequence and length in relatively short pentablock sequences, some of which approach the sequence length of polypeptoid experimental systems. 24,25 Recently, machine learning (ML) models have made important gains in analyzing problems that have resisted treatment by traditional statistical models with examples including speech recognition or image recognition. 26 While neural networks have a long history, the primary reason for this recent surge in advances is the availability of large data sets as well as hardware and algorithmic advances allowing for faster and better fitting of data.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additional work has shown the effect of sequence-tapered blocks at the interface but was limited in the number of sequences examined and did not consider the effects of the sequence along the entirety of one of the blocks . While not explicitly dealing with the precise manipulation of monomer sequence, dissipative particle dynamics simulations have shown differences in self-assembled structures based on block sequence and length in relatively short pentablock sequences, some of which approach the sequence length of polypeptoid experimental systems. , …”
Section: Introductionmentioning
confidence: 99%